Synthesis aspects of cryogenic high-temperature superconducting shielding inductive short-circuit current limiter - Dan’ko, Vladymir Grigorovich; Goncharov, Evgen Viktorovych (Вісник НТУ «ХПІ». Серія: Проблеми удосконалювання електричних машин i апаратiв. Теорiя i практика, 2016)
The short-circuit current limiter of inductive type with the high-temperature superconducting winding and screen is considered. The basic design parameters of the magnetic system were determined and features of the transition process at the initiation of short-circuit were analyzed.